Exploring autonomic modulation: day-to-day recovery after exercise sessions in breast cancer survivors - Lavín-Pérez, Ana Myriam; Collado-Mateo, Daniel; Hinojo González, Carmen; de Juan Ferré, Ana; Ruisánchez Villar, Cristina; Mayo, Xián; Jiménez, Alfonso (Frontiers in Oncology, 2023)
Purpose: The current study aimed to analyze the changes in heart rate variability (HRV) 24h, 48h and 72h after exercise sessions in breast cancer survivors.Methods: Sixteen survivors who had undergone chemotherapy and radiotherapy were included. Participants trained resistance and cardiovascular components 3 times per week. The intervention was supervised and delivered online for 4 weeks. In this period, patients measured their HRV daily, obtaining the lnrMSSD and lnSDNN values of: day 0 (the morning of the training sessions), 24h, 48h and 72h after exercise.Results: Significant changes in lnrMSSD (p=0.015) and lnSDNN (p=0.031) during recovery times and lnSDNN during the weeks were found (p=0.015). The most prominent differences were identified between the baseline measurement taken on day 0 and 24h after exercise (p=0.007 and p=0.048, respectively) and between measurements obtained 24h and 48h after the training session (p=0.019 and p=0.026, respectively).Conclusions: Our study suggests that patients may decrease their lnrMSSD and lnSDNN values 24h after exercise and they were close to recover 48h after the sessions. In this regard, HRV may be an useful tool to monitor their recovery and exercise tolerance.